2022
DOI: 10.1155/2022/3878771
|View full text |Cite
|
Sign up to set email alerts
|

Classification for Memory Activities: Experiments and EEG Analysis Based on Networks Constructed via Phase-Locking Value

Abstract: Electroencephalogram (EEG) plays a crucial role in the study of working memory, which involves the complex coordination of brain regions. In this research, we designed and conducted series of experiments of memory with various memory loads or target forms and collected behavioral data as well as 32-lead EEG simultaneously. Combined with behavioral data analysis, we segmented EEG into slices; then, we calculated phase-locking value (PLV) of Gamma rhythms between every two leads, conducted binarization, construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…They concluded that the Bayesian estimates of the shape and scale parameters would bring smaller mean squared errors with the combination of Type I and Type II progressive hybrid censored data [11]. A 4th-order Butterworth filter was used to extract the EEG components of Gamma rhythm at 30-100 Hz [12]. Then, the extract signal components of Gamma rhythm were segmented with 1 s durations immediately prior to each valid finger clicking moment.…”
Section: Estimation Of Maximum Likelihood and Bayesian Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…They concluded that the Bayesian estimates of the shape and scale parameters would bring smaller mean squared errors with the combination of Type I and Type II progressive hybrid censored data [11]. A 4th-order Butterworth filter was used to extract the EEG components of Gamma rhythm at 30-100 Hz [12]. Then, the extract signal components of Gamma rhythm were segmented with 1 s durations immediately prior to each valid finger clicking moment.…”
Section: Estimation Of Maximum Likelihood and Bayesian Modelmentioning
confidence: 99%
“…The changes of memory activities in the brain can be measured and recorded by EEG signals. In [ 12 ], Xi et al studied the classifications of memory activities with different memory loads or targets based on EEG signal analysis. The memory task experiments simultaneously acquired the 32-lead EEG signals and the corresponding behavioral data from 19 healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations